Navigation-Assisted Full-Endoscopic Radiofrequency Rhizotomy Versus Fluoroscopy-Guided Cooled Radiofrequency Ablation for Sacroiliac Joint Pain Treatment: Comparative Study - Chien-Min Chen; Jae Hwan Lee; Meng-Yin Yang; Shang-Wun Jhang; Kai-Sheng Chang; Su-Wei Ou; Li-Wei Sun; Kuo-Tai Chen (Neurospine, 2023)
Objective Sacroiliac joint (SIJ) pain is a common cause of chronic low back pain. Full-endoscopic rhizotomy of lateral branches of dorsal rami innervating SIJ is a potential option for patients’ refractory to medical treatment. The full-endoscopic rhizotomy is sometimes challenging under fluoroscopic guidance. This study is to evaluate the effectiveness of the navigation-assisted full-endoscopic rhizotomy for SIJ pain. Methods The study was a retrospective match-paired study that enrolled consecutive patients undergoing navigation-assisted full-endoscopic rhizotomy for SIJ pain. The patient demographics, clinical outcomes, and operative parameters of endoscopic rhizotomy were compared with conventional cooled radiofrequency ablation (RFA) treatment. Results The study enrolled 72 patients, including 36 patients in the endoscopic group. Thirty-six patients in the cooled RFA group were matched by age as the control. The follow-up time was at least 1 year. Patient characteristics were similar between the groups. The navigation-assisted endoscopic rhizotomy operation time was significantly longer than the cooled RFA. The visual analogue scale (VAS) for pain and Oswestry Disability Index (ODI) significantly decreased after each treatment. However, the between-group comparison revealed that the VAS and ODI of the patients after endoscopic rhizotomy were significantly lower than those after the cooled RFA group. There were no postoperative complications in the study. Conclusion Navigation-assisted full-endoscopic rhizotomy is an alternative to SIJ pain treatment. Integrating intraoperative navigation can ensure accurate full-endoscopic rhizotomy to provide better durability of pain relief than the cooled RFA.